Do Gender and Academic Anxiety Associate with AI Utilization in English Grammar Courses? - I Komang Adiartha Negara; Ni Made Ratminingsih; Kadek Sintya Dewi (Journal of English Language and Education, 2026)
The growing use of artificial intelligence (AI) in English grammar learning has brought new attention to the role of internal factors in students' use of technology. Although previous studies have focused on demographic and affective variables, the relevance of these factors in a routine academic context still needs to be reviewed. This study examines the relationship between gender and academic anxiety with students’ use of AI-based applications in English Grammar courses. An ex post facto quantitative design was employed involving 123 fourth-semester students majoring in English Education at a public university in North Bali. Data were collected through a survey with questionnaires on academic anxiety and AI utilization, and were analyzed using multiple linear regression. The findings show a relatively similar pattern of AI use among students, indicating that AI functions as an institutionalized learning practice. These results highlight the importance of context and learning design in AI-assisted language learning.